2023
DOI: 10.3390/nano13020362
|View full text |Cite
|
Sign up to set email alerts
|

Fluorometric Sensing and Detection of p-Nitroaniline by Mixed Metal (Zn, Ni) Tungstate Nanocomposite

Abstract: Aromatic amines are important chemical intermediates that hold an irreplaceable significance for synthesizing many chemical products. However, they may react with substances excreted from human bodies to generate blood poisoning, skin eczema, and dermatitis disease and even induce cancer-causing high risks to human health and the environment. Metal tungstates have been proven to be highly efficient materials for developing various toxic gases or chemical detection sensor systems. However, the major factors of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…The process started with a 1:2 molar ratio of zinc nitrate and sodium tungsten oxide dihydrate dissolved in 30 ml DI-H 2 O and mixed for 30 min at ambient temperature. 43 The resulting mixture was then treated with urea and stirred for 30 min. Following the mixture is poured into the Teflon autoclave and moved into the oven at 180 °C for 12 h. The obtained white precipitate was centrifuged and washed multiple times using DI-H 2 O and ethanol to get a pure precipitate.…”
Section: Methodsmentioning
confidence: 99%
“…The process started with a 1:2 molar ratio of zinc nitrate and sodium tungsten oxide dihydrate dissolved in 30 ml DI-H 2 O and mixed for 30 min at ambient temperature. 43 The resulting mixture was then treated with urea and stirred for 30 min. Following the mixture is poured into the Teflon autoclave and moved into the oven at 180 °C for 12 h. The obtained white precipitate was centrifuged and washed multiple times using DI-H 2 O and ethanol to get a pure precipitate.…”
Section: Methodsmentioning
confidence: 99%
“…From the NP-protein potential, the adsorption free energy can be extracted. This in itself provides useful information regarding the affinity of the protein to the NP, and further can be used either to parameterise a second stage of CG NP-protein potential for use in the first type of simulation, or to generate adsorption and desorption rate constants for the RSA model, taking into account the protein serum concentration, sizes of the proteins and NP, and the change in the translational entropy of the proteins [91,93,95]. This approach was found to produce a ranking of proteins adsorbing to silica NPs in broad agreement with that found experimentally, with the disagreement attributed to the neglect of the soft corona in the numerical modelling.…”
mentioning
confidence: 99%
“…Importantly, it was observed that ranking the proteins simply by binding energy did not produce an accurate corona prediction, highlighting the importance of considering the effects of protein serum concentration and the area occupied on the surface of the NP by the protein. The corona formation is known to be highly sensitive to the size of the proteins, especially when the rigidity of the molecules is taken into account, which can be expected from considerations of the entropic effects involved in the corona formation [91,95].…”
mentioning
confidence: 99%